Perancangan Motion Graphic sebagai Pengenalan Kain Tenun Lurik untuk Siswa SMK di Boyolali - Andina Aulia Agustina; Ahmad Khoirul Anwar; Arif Yulianto (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2026)
This final project focuses on designing motion graphics to introduce vocational high school students to lurik woven fabric, especially the Tuluh Watu motif. This design is motivated by the low interest and limited understanding of the younger generation toward lurik fabric compared to batik, especially regarding traditional motifs, so media is needed to attract attention while conveying information clearly. The objective of the design is to produce a digital educational media that is modern, informative, educative, and visually appealing. Motion graphics are designed with a communicative, fun cartoon visual style that combines traditional and modern elements to resonate with vocational high school students. The method used design thinking with five stages, namely empathize, define, ideate, prototype, and test. The empathize stage is carried out through observation, surveys, and interviews to understand the conditions, preferences, and perceptions of students towards lurik fabric, the define stage formulates the main problems and needs of the audience, the ideate stage produces various visual and narrative concepts, and the prototype stage creates an initial version of the motion graphic that combines cartoon animation, Tuluh Watu motif illustrations, warm tertiary colors, and a combination of sans serif and decorative typography. The resulting design consists of a motion graphic concept and prototype that clearly and engagingly introduces the Tuluh Watu motif. It uses a light, communicative visual style, with color and typography that support readability and aesthetics. This creates a modern, informative, and relevant visual medium for vocational school students. Keywords Motion Graphic; Lurik Woven Fabric; Tuluh Watu Motif; Design Thinking; Cartoon Visuals